Culturally Adapted Cognitive-Behavioral Therapy for Chinese Americans With Depression: A Randomized Controlled Trial - Wei-Chin Hwang; Héctor F. Myers; Eddie Chiu; Elsie Mak; Jonathan Butner; Ken Fujimoto; Jeffrey J. Wood; Jeanne Miranda (2015)
No randomized controlled trials (RCTs) for adults have compared the effectiveness of a well-specified psychotherapy and a culturally adapted version of the same treatment. This study evaluated the effectiveness of cognitive-behavioral therapy (CBT) and culturally adapted CBT (CA-CBT) in treating depressed Chinese-American adults.This RCT treated 50 Chinese Americans who met criteria for major depression and sought treatment at community mental health clinics. Screening of participants began in September 2008, and the last assessment was conducted in March 2011. Participants were stratified by whether they were already taking antidepressants when they first came to the clinic and randomly assigned to 12 sessions of CBT or CA-CBT. The study did not influence regular prescription practices. The primary outcomes were dropout rates and Hamilton Depression Rating Scale scores at baseline, session 4, session 8, and session 12.Participants in CA-CBT demonstrated a greater overall decrease in depressive symptoms compared with participants in CBT, but the groups had similarly high depression rates at week 12. Differences in dropout rates for the two groups approached, but did not meet, statistical significance (7%, CA-CBT; 26%, CBT).Chinese Americans entered this study with very severe depression. Participants in both CBT and CA-CBT demonstrated significant decreases in depressive symptoms, but the majority did not reach remission. Results suggest that these short-term treatments were not sufficient to address such severe depression and that more intensive and longer treatments may be needed. Results also indicate that cultural adaptations may confer additional treatment benefits.